Análisis de los Impactos socioambientales producto del funcionamiento de la PTAR salitre. (2022)
Wastewater treatment plants (WWTP) are necessary buildings for environmental sustainability that are the alternative to the recovery of water bodies that a territory possesses and benefits human health, it must be taken into account that these plants can also generate impacts positive and negative on environmental and social aspects.